‘I Like Group Pods’: EFL Students’ Preferences Towards Seating Arrangement in Advanced Speaking Class - Awalyah, Wa Ode Zulhidjah; Sri Wuli Fitriati; Rudi Hartono (English Education Journal, 2023)
This study discussed an EFL student's preferences in using seating arrangements in advanced speaking classes. The lecturers implemented seating arrangements to motivate students and encourage participation. The researcher collected the data through a closed-ended and open-ended questionnaire consisting of two types of classes: basic and advanced speaking classes. This qualitative research used a case study (Heigham & Croker, 2009) as the research design. Data were analyzed using Kember's, theory of motivation and thematic analysis. Then, the data was processed and interpreted qualitatively through the following stages: data transcript, categorizing the codes, analyzing the data, and producing the reports. The findings of this study revealed that from the six types of seating arrangements, the students prefer group pod seating as the type of seating that can build their motivation and active participation in speaking class. Lecturers always use group pod-style seating arrangements in speaking classes. Group pods encourage students to study in class and allow them to collaborate and discuss the topic provided by the lecturer. The seating arrangements make students appear more active when looking in groups. Using this seating type, the students demonstrate their enthusiasm, interact with their classmates by being active participants, pay attention to the lecturer, and understand the lecture's material. This study highlights the necessity for lecturers, higher education institutions, and students to consider various strategies during the learning process.